Cytotoxicity and Antibiofilm Activity of Silver-Polypropylene Nanocomposites - Denise Bellisario; Loredana Santo; Fabrizio Quadrini; Maryam Hassiba; Nour Bader; Shazeda H. Chowdhury; Mohammad K. Hassan; Susu M. Zughaier (MDPI AG, 2023)
The development of biocompatible nanomaterials that interface with human skin and tissue is critical for advancing prosthetics and other therapeutic medical needs. In this perspective, the development of nanoparticles with cytotoxicity and antibiofilm properties and biocompatibility characteristics are important. Metallic silver (Ag) exhibits good biocompatibility, but it is often challenging to integrate it into a nanocomposite without compromising its antibiofilm properties for optimal applications. In this study, new polymer nanocomposites (PNCs) with ultra-low filling content (0.0023-0.046 wt%) of Ag nanoplates were manufactured and tested. The cytotoxicity and antibiofilm activity of different composites with polypropylene (PP) matrix were examined. At first, PNCs surface were analyzed by means of AFM (atomic force microscopy) with phase contrast evaluation and FTIR (Fourier-transform infrared spectroscopy) to study the Ag nanoplates distribution. Subsequently, the cytotoxicity and growth properties of biofilms were assessed by MTT assay protocol and detection of nitric oxide radicals. Antibacterial and antibiofilm activities were measured against Gram-positive bacteria (Staphylococcus aureus) and Gram-negative bacteria (K. pneumoniae). The PNCs with silver exhibited antibiofilm activity although they did not inhibit regular planktonic bacterial growth. Moreover, the PNCs were not cytotoxic to mammalian cells and did not induce significant immune response. These features reveal the potential of the PNCs developed in this study for usage in fabrication of prosthetics and other smart structures for biomedical applications.